2014
DOI: 10.1371/journal.pone.0101902
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cisplatin-Induced Nephrotoxicity and Potential of Magnesium Supplementation for Renal Protection

Abstract: BackgroundNephrotoxicity remains a problem for patients who receive cisplatin chemotherapy. We retrospectively evaluated potential risk factors for cisplatin-induced nephrotoxicity as well as the potential impact of intravenous magnesium supplementation on such toxicity.Patients and MethodsWe reviewed clinical data for 401 patients who underwent chemotherapy including a high dose (≥60 mg/m2) of cisplatin in the first-line setting. Nephrotoxicity was defined as an increase in the serum creatinine concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 31 publications
8
80
1
10
Order By: Relevance
“…The efficacy of administering high-dose cisplatin has been confirmed; however, severe adverse events, including hematotoxicity, anorexia, nausea and nephrotoxicity have been also reported (3,6,7). Large amounts of hydration with saline, mannitol and furosemide are accepted as the standard of care for patients treated with regimens containing high-dose (≥60 mg/m 2 ) cisplatin (3,10,11). Previous studies have demonstrated that Mg supplementation also confers protective effects against cisplatin-induced nephrotoxicity (10,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The efficacy of administering high-dose cisplatin has been confirmed; however, severe adverse events, including hematotoxicity, anorexia, nausea and nephrotoxicity have been also reported (3,6,7). Large amounts of hydration with saline, mannitol and furosemide are accepted as the standard of care for patients treated with regimens containing high-dose (≥60 mg/m 2 ) cisplatin (3,10,11). Previous studies have demonstrated that Mg supplementation also confers protective effects against cisplatin-induced nephrotoxicity (10,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of hydration with saline, mannitol and furosemide are accepted as the standard of care for patients treated with regimens containing high-dose (≥60 mg/m 2 ) cisplatin (3,10,11). Previous studies have demonstrated that Mg supplementation also confers protective effects against cisplatin-induced nephrotoxicity (10,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations